Victimological Analysis of Law No. 31 of 2014 Concerning Protection of Witnesses and Victims - L. Djogo, Arnoldus Thomas; Lawalata, Joey Nicolas; Panjaitan, Junifer Dame (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study aims to analyze Law No. 31 of 2014 concerning the Protection of Witnesses and Victims from a victimological perspective. The methodology employed in this research is a qualitative approach with content analysis of the law text and related literature. The findings indicate that this law provides a stronger legal framework for protecting the rights of victims and witnesses, including the right to physical protection, psychological support, and access to justice. However, despite the clear provisions, the implementation of this law still faces various challenges, such as a lack of public awareness, limited resources, and the social stigma experienced by victims. This study recommends the need for increased legal awareness among the public, as well as training for law enforcement officials, to ensure that the rights of victims and witnesses are effectively protected in the practice of the criminal justice system.